2008
DOI: 10.1016/j.bbabio.2008.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional characterization of FoF1-ATP synthase on the extracellular surface of rat hepatocytes

Abstract: Extracellular ATP formation from ADP and inorganic phosphate, attributed to the activity of a cell surface ATP synthase, has so far only been reported in cultures of some proliferating and tumoral cell lines. We now provide evidence showing the presence of a functionally active ecto-F(o)F(1)-ATP synthase on the plasma membrane of normal tissue cells, i.e. isolated rat hepatocytes. Both confocal microscopy and flow cytometry analysis show the presence of subunits of F(1) (alpha/beta and gamma) and F(o) (F(o)I-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
78
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(84 citation statements)
references
References 36 publications
5
78
1
Order By: Relevance
“…in the absence of a closed vesicle. 38,53 The proposed proteolipidic H þ translocation would help understand extramitochondrial ATP synthases, acting without any transmembrane H þ gradient. The hypothesis that myelin could act like a mitochondrion to contribute to the energetic metabolism of neurons has been criticized by Harris and Attwell.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…in the absence of a closed vesicle. 38,53 The proposed proteolipidic H þ translocation would help understand extramitochondrial ATP synthases, acting without any transmembrane H þ gradient. The hypothesis that myelin could act like a mitochondrion to contribute to the energetic metabolism of neurons has been criticized by Harris and Attwell.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, it reveals the still unrecognized potential of Mitchell's theory, also in being extendable to the emerging awareness of extramitochondrial OXPHOS. 49 New roles emerge for ATP synthases, some of which were recently shown to be ectopically expressed in many cellular membranes where they would conduct extramitochondrial OXPHOS (HUVEC cells, 50 rod outer segments, 51,52 rat hepatocytes, 53 isolated myelin, 54 and cancer cells. 38 In particular, the present hypothesis is consistent with the reported possibility to conduct OXPHOS on a plasma membrane, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that this protein, as part of the whole and active F1/F0 complex, is present on the surface of endothelial cells, tumor cells, [28][29][30] and multiple cell lines. [31][32][33][34] ATP synthase is a protein present on the inner membrane of the mitochondria. The mechanism by which it migrates to the surface of the cell is not understood.…”
Section: Discussionmentioning
confidence: 99%
“…Ca 2+ -ATPase is located in hepatocyte plasma membranes and is involved in calcium homeostasis [57]. A functionally active ecto-F 0 F 1 -ATP synthase has been identified on the plasma membrane of hepatocytes that mediates extracellular formation from ADP and inorganic phosphate [173]. Membrane-bound ATP synthesis has a role in modulating the concentrations of extracellular ADP and is regulated by a plasma apoliproprotein [175].…”
Section: Inflammation Liver Injury and Immune Regulationmentioning
confidence: 99%